Abnormally Elevated Follicle-Stimulating Hormone (FSH) Level in an Infertile Woman - Aurore Catteau; Kalyane Bach-Ngohou; Justine Blin; Paul Barrière; Thomas Fréour; Damien Masson (Case Reports in Endocrinology)
We report a case of 33-year-old woman with a 4-year primary infertility. A high isolated follicle-stimulating hormone (FSH) level was conflicting with the clinical situation and with other hormonal markers which were in favor of polycystic ovarian syndrome. We followed a strategy used to identify immune complexes involving FSH. The PEG precipitation test revealed that the high FSH level was almost exclusively due to the presence of autoimmune FSH immunoglobulin complex (macro-FSH). The profile obtained by gel filtration chromatography confirmed the presence of an FSH-immunoglobulin complex. Such immunological dysregulation could be explored in cases of unexplained infertility and recurrent IVF failure.